THE INFLUENCE OF WORK-LIFE BALANCE AND WORK ENVIRONMENT ON EMPLOYEE JOB SATISFACTION AT BRI BANK PANAKUKKANG BRANCH OFFICE - Nadiyah Nashiroh Bakrie; Tenri S.P. Dipoatmodjo, Zainal Ruma, Muhammad Ichwan Musa, Rezky Amalia Hamka (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of work life balance and work environment on employee job satisfaction at Bank BRI Panakukkang Branch Office. In this study, the population studied amounted to 40 employees who were also sampled. The method used is a quantitative approach with multiple linear regression analysis, using Statistical Product and Service Solution (SPSS) software to analyze the data obtained. Data were collected through questionnaires distributed to respondents involved in this study. The analysis results obtained using the partial test (t test) show that the work life balance and work environment variables partially affect employee job satisfaction based on the value of t count > t table. In the simultaneous test (f test) the work life balance and work environment variables simultaneously have a significant effect on employee job satisfaction based on the value of f count > f table.